The One-State Solution : A Breakthrough for Peace in the Israeli-Palestinian Deadlock - Tilley, Virginia (Book collections on Project MUSE., 2005)
"The One-State Solution explains how Israeli settlements have encroached on the occupied territory of the West Bank and Gaza Strip to such an extent that any Palestinian state in those areas is unworkable. And it reveals the irreversible impact of Israel's settlement grid by summarizing its physical, demographic, financial, and political dimensions." "Virginia Tilley elucidates why we should assume that this grid will not be withdrawn - or its expansion reversed - by reviewing the role of the key political actors: the Israeli government, the United States, the Arab states, and the European Union." "Finally, Tilley focuses on the daunting obstacles to a one-state solution - including major revision of the Zionist dream but also Palestinian and other regional resistance - and offers some ideas about how those obstacles might be addressed."--Jacket